Impacts of DRG-Based Prepayment Reform on the Cost and Quality of Patients with Neurologic Disorders: Evidence from a Quasi-Experimental Analysis in Beijing, China - Cao Z; Liu X; Wang X; Guo M; Guan Z (Dove Medical Press, 2024)
Zhen Cao,1 Xiaoyu Liu,2 Xiangzhen Wang,3 Moning Guo,4 Zhongjun Guan1,5 1School of Public Health, Capital Medical University, Beijing, People's Republic of China; 2School of Statistics, Capital University of Economics and Business, Beijing, People's Republic of China; 3School of Public Health, Peking University Health Science Center, Beijing, People's Republic of China; 4Beijing Municipal Health Big Data and Policy Research Center, Beijing, People's Republic of China; 5Beijing Tiantan Hospital, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Moning Guo, Beijing Municipal Health Big Data and Policy Research Center, No. 277, Zhao Dengyu Road, Xicheng District, Beijing, 100053, People's Republic of China, Email guomoning@wjw.beijing.gov.cn Zhongjun Guan, Beijing Tiantan Hospital, Capital Medical University, No. 119, South Fourth Ring West Road, Fengtai District, Beijing, 100070, People's Republic of China, Email guanzhj@ccmu.edu.cnPurpose: As one of the pioneering pilot cities in China's extensive Diagnosis Related Groups (DRG) -based prepayment reform, Beijing is leading a comprehensive overhaul of the prepayment system, encompassing hospitals of varying affiliations and tiers. This systematic transformation is rooted in extensive patient group data, with the commencement of actual payments on March 15, 2022. This study aims to evaluate the effectiveness of DRG payment reform by examining how it affects the cost, volume, and utilization of care for patients with neurological disorders.Patients and Methods: Utilizing the exogenous shock resulting from the implementation of the DRG-based prepayment system, we adopted the Difference-in-Differences (DID) approach to discern changes in outcome variables among DRG payment cases, in comparison to control cases, both before and following the enactment of the DRG policy. The analytical dataset was derived from patients diagnosed with neurological disorders across all hospitals in Beijing that underwent the DRG-based prepayment reform. Strict data inclusion and exclusion criteria, including reasonableness tests, were applied, defining the pre-reform timeframe as March 15th through October 31st, 2021, and the post-reform timeframe as the corresponding period in 2022. The extensive dataset encompassed 53 hospitals and encompassed hundreds of thousands of cases.Results: The implementation of DRG-based prepayment resulted in a substantial 12.6% decrease in total costs per case and a reduction of 0.96 days in length of stay. Additionally, the reform was correlated with significant reductions in overall in-hospital mortality and readmission rates. Surprisingly, the study unearthed unintended consequences, including a significant reduction in the proportion of inpatient cases classified as surgical patients and the Case Mix Index (CMI), indicating potential strategic adjustments by providers in response to the introduction of DRG payments.Conclusion: The DRG payment reform demonstrates substantial effects in restraining cost escalation and enhancing quality. Nevertheless, caution must be exercised to mitigate potential issues such as patient selection bias and upcoding.Keywords: diagnosis-related groups, payment reform, neurological disorders, DID, China